Yudas Iskariot dan Narasi Pengampunan: Menggugat Finalitas Penghakiman dalam Tradisi Kristen - Tiopan Aruan (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2026)
Abstract. The figure of Judas Iscariot has historically been labeled as a symbol of failure, betrayal, and eternal damnation. In many Christian traditions, the narrative of Judas Iscariot concludes with the final judgment, leaving no room for restoration or forgiveness. This article intends to challenge that understanding through a narrative approach and a hermeneutic of forgiveness, by re-examining the story of Judas Iscariot from theological, ethical, and pastoral perspectives. It compares the responses of remorse shown by Judas Iscariot and Peter, while also exploring insights from theologians such as Karl Barth, David Bentley, and Miroslav Volf. Thus, this paper highlights the possibility of forgiveness within God's plan of salvation—even for the “son of perdition.”Abstrak. Tokoh Yudas Iskariot secara historis telah dilabel sebagai simbol kegagalan, pengkhianatan, dan kebinasaan kekal. Dalam banyak tradisi Kristen, narasi tentang Yudas Iskariot berujung pada finalitas hukuman, tanpa ruang untuk pemulihan atau pengampunan. Artikel ini berupaya menantang pemahaman tersebut melalui pendekatan naratif dan hermeneutika pengampunan, dengan menelaah kembali kisah Yudas Iskariot secara teologis, etis, dan pastoral, dan dengan membandingkan respons penyesalan Yudas Iskariot dan Petrus serta mengeksplorasi pemikiran dari teolog-teolog seperti Karl Barth, David Bentley, dan Miroslav Volf. Dengan demikian, tulisan ini menyoroti kemungkinan adanya ruang pengampunan dalam rencana keselamatan Allah, bahkan bagi “anak kebinasaan” sekalipun.